Comparative nutritional evaluation of the leaves of selected plants from the Poaceae family (bamboos and grasses) for sustainable livestock production in Ghana - Sasu, Prince; Attoh-Kotoku, Victoria; Anim-Jnr, Antoinette S.; Osman, Alhassan; Adjei, Obed; Adjei-Mensah, Benjamin; Edinam Aku Akoli, Dora; Adjima Tankouano, Rachida; Kwaku, Michael; Obloni Kweitsu, Daniel (Frontiers in Sustainable Food Systems, 2023)
Background Sustainable animal feeding is essential for reducing poverty among Ghanaian smallholder livestock farmers. However, seasonality has a severe impact on the availability and quality of conventional animal feedstuffs, necessitating alternate feed sources. Objective This study evaluated and compared the nutritional characteristics of the leaves of three bamboo species namely; Bambusa balcooa (Beema), Oxytenanthera abyssinica (A. Rich.) Munro and Bambusa vulgaris; and three conventional types of grass, namely; Cenchrus purpureus, Megathyrsus maximus, and Brachiaria decumbens. Materials and methods The plant biomasses were subjected to the standard analytical procedures of proximate and detergent fiber systems to highlight their dry matter (DM), crude protein (CP), crude fiber (CF), ether extract (EE), ash, nitrogen-free extract (NFE), neutral detergent fiber (NDF), acid detergent fiber (ADF), and acid detergent lignin (ADL). Other nutritional characteristics were estimated using the chemical compositions. Statistical analysis Data was analyzed using Generalized Linear Model procedures in Minitab Statistical Software at a 5% significant level. Results Results showed a significantly (P < 0.05) higher DM ( 918 g/kgDM), CP ( 153 g/kgDM), and EE ( 153 g/kgDM) in B. vulgaris leaves. O. abyssinica leaves had the maximum ash ( 139 g/kgDM) while those of M. maximus had the highest carbohydrate ( 709 g/kgDM) and CF ( 492 g/kgDM). Compared to the grasses, the bamboo had a higher pool of DM ( 910 vs. 836 g/kgDM), CP ( 133 vs. 75 g/kgDM), EE ( 137 vs. 82 g/kgDM), ash ( 134 vs. 89 g/kgDM), hemicellulose ( 79 vs. 28 g/kgDM), dry matter intake ( 25 vs. 24%), digestible dry matter ( 58 vs. 53%), and relative feed value ( 111 vs. 105). In contrast, the grasses had higher mean ADF ( 461 vs. 402 g/kgDM), cellulose ( 417 vs. 397 g/kgDM), and ADL ( 5 vs. 0.4 g/kgDM). Conclusion The study suggests that bamboo leaves could have high nutritional characteristics to supplement or even replace conventional grasses and other crop residues in the diets of ruminants, especially during the dry season.